Test method for determining hardenability of aluminum alloy

By performing solid solution and aging heat treatment, conductivity and hardness test and tensile performance test on aluminum alloy workpieces, the problem of limits in hardenability determination of end quenching is solved, and the accurate evaluation of the hardenability of aluminum alloy and the actual production consistency of the process are achieved.

CN119901616APending Publication Date: 2025-04-29JIANGXI HONGDU AVIATION IND GRP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510229890.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing end quenching method is used to determine the hardenability of aluminum alloys, which is difficult to accurately reflect the quenching situation in the actual production process, and the evaluation criteria do not meet the actual production requirements.

Method used

A test method for determining the hardenability of aluminum alloy is adopted, including preparing cylindrical aluminum alloy workpieces for solid solution and aging heat treatment, followed by conductivity and hardness tests and tensile performance tests, and the hardenability is determined through a curve chart.

Benefits of technology

This method can directly and accurately simulate the actual quenching of aluminum alloy workpieces, effectively evaluate the hardenability, and ensure the consistency of the process and actual production. It is suitable for the hardenability research of aluminum alloys and other materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901616A_ABST
    Figure CN119901616A_ABST
Patent Text Reader

Abstract

The invention discloses a test method for determining the hardenability of an aluminum alloy. The method comprises the following steps: (1) preparing an aluminum alloy workpiece; (2) the aluminum alloy workpiece in the step (1) is subjected to solid solution and aging heat treatment according to the process file requirement; (3) testing conductivity and hardness; (4) carrying out a tensile property test; (5) drawing a curve graph to determine the hardenability of the aluminum alloy material; the method has the advantages that the actual quenching condition in the production process of the aluminum alloy workpiece can be directly and accurately simulated, the hardenability of the aluminum alloy material can be effectively evaluated, the consistency of the process and actual production can be guaranteed, and the production efficiency is improved. And a powerful technical support is provided for optimization of an aluminum alloy quenching process in the fields of aerospace and the like. And meanwhile, the method is high in applicability and can be applied to hardenability research of materials such as steel and titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat treatment of metal materials, and specifically relates to a test method for determining the hardenability of aluminum alloy. Background Art

[0002] There is no complete test and evaluation system for the hardenability of aluminum alloys. The determination and test methods of aluminum alloy hardenability mainly come from heat treatment of steel. The physical meaning of steel hardenability is very clear, that is, the distance from the surface of the part to the semi-martensite zone (that is, martensite and troostite or other tissues each account for 50%) is measured as the hardenability depth, so the hardenability depth of steel is relatively easy to measure using the metallographic hardness method. However, what remains after quenching of aluminum alloy is a supersaturated solid solution, and its supersaturation is difficult to observe and test using a microscope. At the same time, it is also quite difficult to sample and measure the isothermal transformation C curve of aluminum alloy similar to the determination of the isothermal transformation C curve of alloy steel. Therefore, there are few detailed reports on the hardenability of aluminum alloys, both at home and abroad. There is no systematic report on the physical meaning of the hardenability of aluminum alloys, the provisions of the hardenability depth and the C curve.

[0003] By consulting relevant literature, some researchers have used the end quenching method, a test method for the hardenability of steel materials, to determine the hardenability of aluminum alloy materials, and used a 10% drop in maximum hardness as the standard for hardenability. The end quenching method is easy to operate and has strong applicability. However, during the test, the main cooling source of the sample is only one surface in contact with the cooling medium, which is different from the cooling method of the entire part in contact with the cooling medium during the actual part production process. In addition, the end quenching method uses small-sized samples, and the organizational structure and performance parameters obtained after heat treatment are different from the actual situation of large-sized aluminum alloy workpieces. In summary, there are certain limitations in using the end quenching method to test the hardenability of metal materials. At the same time, the end quenching method requires the use of special quenching equipment, and the quenching process conditions are harsh. It is difficult to track the actual heat treatment quenching production process. It is a simulated quenching process method. At the same time, the cooling conditions at the end face may not match the actual quenching process conditions due to end face quenching, which may cause other errors. In existing studies, some scholars have used a 10% drop in the maximum hardness of aluminum alloy specimens as the standard for hardening. This criterion has limitations in its application in actual production and is inconsistent with the actual production requirement that the core meet the design performance requirements. Summary of the invention

[0004] The purpose of the present invention is to overcome the technical deficiencies of the end quenching method for testing the hardenability, and to provide a quenching effect test and test evaluation method for aluminum alloy materials suitable for actual production, which can intuitively and effectively test the actual quenching conditions of aluminum alloy materials, and the test results can be directly applied to the formulation of quenching technology in actual production.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a test method for determining the hardenability of aluminum alloy, the method comprising the following steps: (1) preparing an aluminum alloy workpiece: wherein the shape of the aluminum alloy workpiece is cylindrical, the height of the aluminum alloy workpiece is equal to the diameter of the aluminum alloy workpiece, and the diameter of the aluminum alloy workpiece is the maximum effective thickness of the aluminum alloy used by the production unit; (2) performing solid solution and aging heat treatment: performing solid solution and aging heat treatment on the aluminum alloy workpiece in step (1) according to the requirements of the process document; (3) Conduct conductivity and hardness test: according to Figure 1 The sampling method shown is to take out a test piece from the center of the cylindrical aluminum alloy workpiece after the heat treatment in step (2) for hardness and conductivity testing, and select points equidistant from the end surface of the test piece to the core in the length direction of the test piece for hardness and conductivity testing; (4) Conduct tensile performance test: After the conductivity and hardness tests are completed, the test pieces that have undergone the hardness and conductivity tests in step (3) are Figure 2 The sampling method shown in the figure is to cut the tensile test specimens from the end surface of the test piece to the core at equal distances, and then press each cut tensile test specimen Figure 3 As shown in the schematic diagram, they are processed into standard tensile test bars, and the tensile strength values ​​of the tensile test bars are tested according to the tensile test standard requirements; (5) Drawing a graph: With the distance from the test piece surface as the horizontal axis and the hardness value, conductivity value and tensile strength value at different distances from the test piece surface as the vertical axis, the measured hardness values, conductivity values ​​and tensile strength values ​​at different locations on the test piece surface are connected into a broken line to obtain the hardness value curve, conductivity value curve and tensile strength value curve of the aluminum alloy workpiece that change with the surface distance, thereby determining the hardenability of the aluminum alloy material.

[0006] Furthermore, in step (1), the aluminum alloy workpiece is a heat-treatable and hardened aluminum alloy.

[0007] Furthermore, in step (1), the aluminum alloy workpiece is obtained by hot rolling, forging or casting.

[0008] Furthermore, in step (2), the equipment used for the solution heat treatment is a nitrate tank or an air circulation electric furnace, the heating temperature is 465~535℃, the specific solution temperature and holding time are determined according to the material type, and after solution treatment, aging strengthening is carried out according to standard requirements.

[0009] Furthermore, in step (3), the dimensions of the test piece are: 32-100 mm in width, 10-15 mm in thickness, and the same length as the diameter of the cylindrical aluminum alloy workpiece, wherein the width of the test piece is not less than the length of the tensile test bar required by the standard.

[0010] Furthermore, in step (4), the tensile test bar is a standard specimen in the national standard GB / T 228.1 Metallic material tensile test part 1: Room temperature test method.

[0011] In the present invention, in step (5), the method is suitable for direct testing and research on the quenching effect of heat treatment on aluminum alloy materials. By comparing the hardenability of aluminum alloys under different quenching conditions (such as solution temperature, cooling method, quenching medium temperature, etc.), the acceptance value of the heat treatment standard of aluminum alloy materials is used as the evaluation standard of the hardenability of aluminum alloys, thereby ensuring the consistency between the process and actual production, and providing strong technical support for the optimization of aluminum alloy quenching process in the fields of aerospace and aviation.

[0012] The hardenability testing method of the present invention can be applied not only to aluminum alloy materials, but also to the hardenability research of materials such as steel, titanium alloy, etc.

[0013] The beneficial effects of the invention are as follows: the method of the invention can directly and accurately simulate the actual quenching conditions in the production process of aluminum alloy workpieces, which can not only effectively evaluate the hardenability of aluminum alloy materials, but also ensure the consistency of the process with actual production, and provide strong technical support for the optimization of aluminum alloy quenching process in the fields of aerospace and aviation. At the same time, the inventive method has strong applicability and can be applied to the hardenability research of materials such as steel and titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram of processing the conductivity and hardness test piece of the present invention; Figure 2 It is a schematic diagram of processing the tensile property test specimen of the present invention; Figure 3 It is a structural schematic diagram of the tensile test bar of the present invention; Figure 4 A curve diagram showing the hardness value of LY12 aluminum alloy as the distance from the surface changes in Example 1 of the present invention; Figure 5 The conductivity value curve of LY12 aluminum alloy according to the surface distance in Example 1 of the present invention is shown; Figure 6 A curve diagram showing the change in tensile strength value of LY12 aluminum alloy with surface distance in Example 1 of the present invention; Figure 7 A curve diagram showing the hardness value of LC4 aluminum alloy as the distance from the surface changes in Example 2 of the present invention; Figure 8 The conductivity value curve of LC4 aluminum alloy according to the surface distance in Example 2 of the present invention is shown; Fig. 9This is a curve diagram of the tensile strength value of LC4 aluminum alloy in Example 2 of the present invention as the surface distance changes. DETAILED DESCRIPTION

[0015] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention. Example

[0016] like Figures 1 to 9 As shown, the present invention provides a test method for determining the hardenability of aluminum alloy, the method comprising the following steps: (1) Take a hot-rolled LY12 bar with a diameter of 160 mm and a height of 160 mm; (2) The LY12 bar of step (1) is subjected to a solution and aging heat treatment, the equipment used for the solution treatment is a nitrate tank, the solution temperature is 495°C, the holding time is 90-92 min, the heating medium is nitrate, the cooling medium is 29.9°C tap water, and the aging process is natural aging for 96 h; (3) After aging, press Figure 1 Sampling method: Cut a test piece of 160mm long, 60mm wide and 10mm thick, and start from 15mm away from the edge of the test piece surface, select points every 5mm along the length direction of the test piece to conduct hardness test towards the core, and select points every 10mm along the length direction of the test piece to conduct conductivity test towards the core; (4) Then, the test pieces that have been tested for hardness and conductivity are placed in accordance with Figure 2 The sampling method shown in the figure is to cut the tensile test specimens at a distance of 10 mm along the length of the test specimen starting from 15 mm away from the edge of the test specimen surface, and then press Figure 3 As shown in the schematic diagram, a standard tensile test bar is processed and the tensile test bar is tested for its tensile strength value, wherein the tensile test bar is a standard specimen in the national standard GB / T 228.1 Metallic material tensile test part 1: Room temperature test method; (5) The hardness values ​​and conductivity values ​​at different locations from the surface of the test specimen measured in step (3) are connected into a broken line to obtain a hardness value curve graph of LY12 aluminum alloy with the distance from the surface (the broken line graph is shown in FIG. Figure 4 ) and the conductivity curve of LY12 aluminum alloy with the change of surface distance (line graph as shown Figure 5 As shown in FIG. 1 ), the tensile strength values ​​at different locations from the surface of the test specimen measured in step (4) are connected into a broken line to obtain a curve of the tensile strength value of LY12 aluminum alloy varying with the distance from the surface. The broken line graph is shown in FIG. Figure 6 shown.

[0017] Preferably, the acceptance values ​​of the heat treatment standard of LY12 aluminum alloy are: hardness value of 63~82HRB, conductivity value of 28.5~33.5%iACS, and tensile strength value / Rm of ≥390MPa. It is evaluated that the LY12 aluminum alloy bar in hot-rolled state with a diameter of 160mm can be fully hardened under the above heat treatment conditions. Example

[0018] like Figures 1 to 9 As shown, the present invention provides a test method for determining the hardenability of aluminum alloy, the method comprising the following steps: (1) Take a hot-rolled LC4 bar with a diameter of 150 mm and a height of 150 mm; (2) subject the LC4 bar of step (1) to solid solution and aging heat treatment, the equipment used for solid solution is a nitrate tank, the solid solution temperature is 470°C, the holding time is 80-82 min, the heating medium is nitrate, and the cooling medium is 29.8°C tap water; the equipment used for aging is an air circulation electric furnace, the aging temperature is 120°C, and the temperature is kept for 3-3.5 hours, and then kept at 160°C for 3-3.5 hours; (3) After aging, press Figure 1 Sampling method: Cut a test piece of 150mm long, 60mm wide and 10mm thick, and start from 15mm away from the edge of the test piece surface, select points every 5mm along the length direction of the test piece to conduct hardness test towards the core, and select points every 10mm along the length direction of the test piece to conduct conductivity test towards the core; (4) Then, the test pieces that have been tested for hardness and conductivity are placed in accordance with Figure 2 The sampling method shown in the figure is to cut the tensile test specimens at a distance of 10 mm along the length of the test specimen starting from 15 mm away from the edge of the test specimen surface, and then press Figure 3 As shown in the schematic diagram, a standard tensile test bar is processed and the tensile test bar is tested for its tensile strength value, wherein the tensile test bar is a standard specimen in the national standard GB / T 228.1 Metallic material tensile test part 1: Room temperature test method; (5) The hardness values ​​and conductivity values ​​at different locations from the surface of the test specimen measured in step (3) are connected into a broken line to obtain a hardness value curve graph of LC4 aluminum alloy with the distance from the surface (the broken line graph is shown in FIG. Figure 7 ) and the conductivity curve of LC4 aluminum alloy with the change of surface distance (line graph as shown Figure 8 As shown in FIG. 1 ), the tensile strength values ​​at different locations from the surface of the test specimen measured in step (4) are connected into a broken line to obtain a curve of the tensile strength value of the LC4 aluminum alloy varying with the distance from the surface. The broken line graph is shown in FIG. Fig. 9 shown.

[0019] Preferably, the acceptance values ​​of the LC4 aluminum alloy heat treatment standard are: hardness value of 82~93HRB, conductivity value of 30.5~35.5%iACS, tensile strength value / Rm of ≥530MPa. It is evaluated that the LC4 aluminum alloy bar with a diameter of 150mm in hot-rolled state can be fully hardened under the above heat treatment conditions.

[0020] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

[0021] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and to form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A test method for determining the hardenability of aluminum alloy, characterized in that: The method comprises the following steps: (1) preparing an aluminum alloy workpiece: wherein the shape of the aluminum alloy workpiece is cylindrical, the height of the aluminum alloy workpiece is equal to the diameter of the aluminum alloy workpiece, and the diameter of the aluminum alloy workpiece is the maximum effective thickness of the aluminum alloy used by the production unit; (2) performing solid solution and aging heat treatment: performing solid solution and aging heat treatment on the aluminum alloy workpiece in step (1) according to the requirements of the process document; (3) Conducting conductivity and hardness tests: taking out a test piece from the center of the cylindrical aluminum alloy workpiece after the heat treatment in step (2) for hardness and conductivity tests, and selecting points equidistant from the end surface of the test piece toward the core in the length direction of the test piece for hardness and conductivity tests; (4) Conducting a tensile performance test: After the conductivity and hardness tests are completed, the test piece that has undergone the hardness and conductivity tests in step (3) is cut into tensile performance test specimens at equal distances from the end surface of the test piece surface to the core, and then each of the cut tensile performance test specimens is processed into a standard tensile test bar, and the tensile strength value of the tensile test bar is tested according to the tensile test standard requirements; (5) Drawing a graph: With the distance from the test piece surface as the horizontal coordinate, and the hardness value, conductivity value, and tensile strength value at different distances from the test piece surface as the vertical coordinate, the measured hardness values, conductivity values, and tensile strength values ​​at different locations on the test piece surface are connected into a broken line to obtain the hardness value curve, conductivity value curve, and tensile strength value curve of the aluminum alloy workpiece that change with the surface distance, thereby determining the hardenability of the aluminum alloy material.

2. The test method for determining the hardenability of aluminum alloy according to claim 1, characterized in that: In step (1), the aluminum alloy workpiece is a heat-treatable and hardened aluminum alloy.

3. The test method for determining the hardenability of aluminum alloy according to claim 1, characterized in that: In step (1), the aluminum alloy workpiece is obtained by hot rolling, forging or casting.

4. The test method for determining the hardenability of aluminum alloy according to claim 1, characterized in that: The equipment used for solution heat treatment is a nitrate tank or an air circulation electric furnace. The heating temperature is 465~535℃. The specific solution temperature and holding time are determined according to the material type. After solution treatment, aging strengthening is carried out according to standard requirements.

5. The test method for determining the hardenability of aluminum alloy according to claim 1, characterized in that: In step (3), the dimensions of the test piece are: 32-100 mm in width, 10-15 mm in thickness, and the same length as the diameter of the cylindrical aluminum alloy workpiece, wherein the width of the test piece is not less than the length of the tensile test bar required by the standard.

6. The test method for determining the hardenability of aluminum alloy according to claim 1, characterized in that: In step (4), the tensile test bar is a standard specimen in the national standard GB / T 228.1 Metallic material tensile test part 1: Room temperature test method.

Citation Information

Patent Citations

  • Experimental method for measuring harden ability of large-sized aluminium alloy

    CN101788438A

  • Method suitable for directly testing and evaluating quenching effect of aluminum alloy material

    CN102445400A

  • Method for rapid evaluation of hardenability of 20CrMnTi series steel

    CN104914228A

  • Method for detecting hardenability of steel

    CN116397078A

  • Heat treatment process for improving comprehensive mechanical properties of 12CrNi5MoV steel forgings

    CN117551943A